CREATIVE ACCOUNTING PRACTICIES IN SLOVAKIA AFTER PASSING FINANCIAL CRISIS - Škoda, Miroslav; Lengyelfalusy, Tomáš; Gabrhelová, Gabriela (Copernican Journal of Finance & Accounting, 2017)
Fraud in economics and accounting is the practice which is adopted within the framework of accounting system or in other words taking undue advantage of loopholes of accounting system is creative accounting. In highly competitive market, it becomes very important and necessary for every business to find new and innovative ways of running the business. And one of the new ways is creative accounting. Creative accounting is an art of manipulating the books of accounts in a manner that desired results can be drawn. Aggressive accounting, cooking the books and massaging the numbers are few common terms used in context of creative accounting. Creative accounting in present uncertain environment is facilitating management to accomplish personal goals as big, well established firms followed.